1994
DOI: 10.3109/10408419409113559
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of Explosives and Related Compounds

Abstract: The pollution of soil and water with explosives and related compounds caused by military activities has been known for a long time, but progress in understanding the environmental fate of such substances has only been made in the last few years. Microbial processes could be used for the remediation of explosives-contaminated soils and waste waters because it has been shown that a variety of different microorganisms are able to metabolize these chemical compounds. In some cases even a complete mineralization ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(113 citation statements)
references
References 78 publications
1
112
0
Order By: Relevance
“…Gordonia sp. KTR9; Thompson et al, 2005;Gorontzy et al, 1994). All these data show the richness of metabolic activities of gordoniae and widen our view about the possible industrial and environmental application of these bacteria.…”
mentioning
confidence: 91%
“…Gordonia sp. KTR9; Thompson et al, 2005;Gorontzy et al, 1994). All these data show the richness of metabolic activities of gordoniae and widen our view about the possible industrial and environmental application of these bacteria.…”
mentioning
confidence: 91%
“…All the methods possess significant differences in color removal results, volume capability, operating time and capital costs. White rot fungi have been studied for their ability to degrade recalcitrant organo-pollutants such as polycyclic aromatic hydrocarbons (Bogan & Lamar, 1996), chlorinated phenols (Ruckenstein & Wang, 1994), PCBs (Sasek et al, 1993, Beaudette et al, 1998, dioxins (Takada et al, 1996), pesticides (Kullman & Matsumura, 1996), explosives (Gorontzy et al, 1994), dichloroaniline (Arjmand & Sandermann, 1985) and dyes (Kirby et al, 1995, Shin et al, 1997, Rodriguez et al, 1999. From the analysis of literature it is found that many authors used white rot fungi for decolorization of textile effluents (Chagas & Durrant, 2001 Though the number of studies on the biodegradation of dyestuffs have been steadily increasing in recent years, very few researches are reported for biodegradation of azo dyes, such as Cibacron Yellow S-3R using white rot fungi (Yesilada et al, 1998) and hence in this present research an attempt has been made to investigate the biological decolorization of the azo dye Cibacron Yellow S-3R using Coriolus Versicolor (MTCC 138).…”
Section: Introductionmentioning
confidence: 99%
“…Hexahydro-l,3,5-trinitro-l,3,5-triazine (RDX), octahydro-l,3,5,7-tetranitro-l,3,5,7-tetrazocine (HMX), and 2,4,6-trinitrotoluene (TNT) are secondary high explosives widely used by militaries throughout the world [1]. Wastewater contaminated with these explosives is generated during the production of munitions, as well as from demilitarization operations when excess or outdated munitions are destroyed [2].…”
Section: Introductionmentioning
confidence: 99%